Hardware Description Languages in Modern Digital Design - Shadiyeva Marjona (Scientific Trends, 2025)
Hardware Description Languages also known as HDLs have become a breakthrough in the world of engineering by transforming the way digital systems are designed and implemented. As technology becomes increasingly complex, traditional schematic-based design methods are no longer sufficient to describe complex hardware systems. HDLs have emerged as tools that address this problem since they provide efficient and structured ways to describe circuits at various abstraction levels and enable the synthesis of these descriptions into real hardware. This paper aims to demonstrate the importance of using HDLs in designing modern digital systems by outlining types of HDLs, their use in hierarchical and modular design, verification, simulation and synthesis processes. The examination of the role of HDLs demonstrates that they have become crucial in digital design due to their ability to provide a framework for transforming mere descriptions into real-life circuits.